History of the Development of Islamic Education in Sumatra (A Study of Figures and Institutions) - Amri Usa; Bahaking Rama; Syamsuddin (Pustaka Digital Indonesia, 2025)
This study aims to discuss the history of the development of Islamic education in Sumatra, this research focuses on the study of Islamic figures and institutions that have developed since the early arrival of Islam in Sumatra to the present. This study uses a qualitative method, with reference to the data obtained from the search results of the literature study. The results of the study show that 1. Islam entered Minangkabau between the 12th and 13th centuries AD, through two routes namely; the route from Aceh and the path from Malacca which was introduced by merchants from Arabia. 2. Surau (as the oldest educational institution) for the Minangkabau people has a multidimensional function, not only serving as a gathering place, meeting and sleeping place but also functioning as an Islamic educational institution. 3. Among the well-known Minangkabau Islamic figures since the early arrival of Islam, among others, Shaykh Burhanuddin (1680 AD), Shaykh Abdulrahman (1777), Haji Piobang from Agam, Haji Poor from Pandai Sikek and Haji Sumanik from Batusangkar (1803)